PENINGKATAN KARAKTER TANGGUNG JAWAB MELALUI METODE PROYEK PADA ANAK KELOMPOK B TK MARFU’AH PALEMBANG - Seftyana, Mega - (Universitas sriwijaya, 2018)
This type of research is a classroom action research entitled Character building Responsibility through Project Methods In Child Group B TK Marfu’ah Palembang, aims to improve the character of responsibility through the project method. The subjects of this study were children aged (5-6) years of 16 children consisting of 8 boys and 8 girls in this the academic year 2016-2017. Data collection techniques use observation and test sheets. The result of data analysis indicate that there is an increase of responsibility character from Cycle I, Cycle II, Cycle III, Cycle IV as follows: in Cycle I there are 5 children (31%) who get minimum score with criteria developed according to expectation (BSH). In Cycle II there were 9 children (56%) who got the minimum score with the criteria developed according to expectations (BSH). In Cycle III, there were 11 children (69%) who got the minimum score with the got the minimum developed according to expectations (BSH). And in Cycle IV there are children (82%) who get the minimum score with the criteria developing as expectations (BSH). Based on the criteria that have been set that is at least 75% of children in the class get the minimum value to grow as expected. For that in Cycle IV the study was stopped. This can be proved by the dominant indicator arising from Cycle I to Cycle IV that often arises is the child doing the task and completing the task, while the indicator that has not appeared in every cycle is to accept the consequenses and indicators that appear less ineach cycle is to get the results the maximum. For that it is necessary to suggest for further researcher to do research of class action to improve character of responsibility in indicator to get maximum result